2018
DOI: 10.3390/environments5080089
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Waste Management: A Case Study from Sudan

Abstract: Healthcare waste (HCW) represents a major public health issue, especially in developing countries. Among HCW categories, sharps waste is one of the most hazardous. Exposure to needle-stick injuries can lead to blood-borne pathogens, therefore HCW should be managed in an effective manner. The main aims of this study were to assess the current management of used needles and to suggest suitable recommendations for an improved and safer system for needle management in Khartoum, Sudan. The study showed that the man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…Majority of laboratories staff are separating the medical sharps from other types of wastes in safety boxes and get rid of it by specialized company in medical waste. Few laboratories throw the safety box in landfill and reuse the safety box again and others burring or burning it as shown in figure (3,4).Majority of laboratory staff they don't know how to manage chemical waste as presented in table (2). Regarding chemical and biological waste there is variation in disposal methods as shown in table (3,4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Majority of laboratories staff are separating the medical sharps from other types of wastes in safety boxes and get rid of it by specialized company in medical waste. Few laboratories throw the safety box in landfill and reuse the safety box again and others burring or burning it as shown in figure (3,4).Majority of laboratory staff they don't know how to manage chemical waste as presented in table (2). Regarding chemical and biological waste there is variation in disposal methods as shown in table (3,4).…”
Section: Resultsmentioning
confidence: 99%
“…Hassan AA et al found that Sharps management is inefficient in Khartoum hospitals. as all wastes are gathered without separation and disposed improperly, especially needles (4).…”
Section: Discussionmentioning
confidence: 99%
“…The study observed that a low level of HBV vaccination and high rates of needlestick injuries existed among the health workers examined in the study. Furthermore, Hassan et al [35] admitted that healthcare workers in Sudan are at high risk of contamination with medical waste generated from hospital activities. The authors avowed that lack of waste segregation, lack of waste management policies, and failure to plan are critical factors.…”
Section: Current Status Of Ohs Research In Sudanmentioning
confidence: 99%
“…Hassan et al 2018 [18] focus on assessing existing management of approaches for used needles in Khartoum, Sudan and proposing suitable recommendations for an improved and safer system for needle management.…”
Section: Highlightsmentioning
confidence: 99%